Effect of surface modifications on the bond strength of zirconia ceramic with resin cement resin. Issue 5 (May 2016) - Hallmann, Lubica; Ulmer, Peter; Lehmann, Frank; Wille, Sebastian; Polonskyi, Oleksander; Johannes, Martina; Köbel, Stefan; Trottenberg, Thomas; Bornholdt, Sven; Haase, Fabian; Kersten, Holger; Kern, Matthias
Abstract: Objectives: Purpose of this in vitro study was to evaluate the effect of surface modifications on the tensile bond strength between zirconia ceramic and resin. Methods: Zirconia ceramic surfaces were treated with 150-μm abrasive alumina particles, 150-μm abrasive zirconia particles, argon-ion bombardment, gas plasma, and piranha solution (H2 SO4 :H2 O2 = 3:1). In addition, slip casting surfaces were examined. Untreated surfaces were used as the control group. Tensile bond strengths (TBS) were measured after water storage for 3 days or 150 days with additional 37, 500 thermal cycling for artificial aging. Statistical analyses were performed with 1-way and 3-way ANOVA, followed by comparison of means with the Tukey HSD test. Results: After storage in distilled water for three days at 37 °C, the highest mean tensile bond strengths (TBS) were observed for zirconia ceramic surfaces abraded with 150-μm abrasive alumina particles (TBSAAP = 37.3 MPa, TBSCAAP = 40.4 MPa), and 150-μm abrasive zirconia particles (TBSAZP = 34.8 MPa, TBSCAZP = 35.8 MPa). Also a high TBS was observed for specimens treated with argon-ion bombardment (TBSBAI = 37.8 MPa). After 150 days of storage, specimens abraded with 150-μm abrasive alumina particles and 150-μm abrasive zirconia particles revealed high TBS (TBSAAP = 37.6 MPa, TBSCAAP = 33.0 MPa, TBSAZP = 22.1 MPa and TBSCAZP = 22.8 MPa). A high TBS was observed also for specimens prepared with slip casting (TBSSC = 30.0 MPa). A decrease of TBS was observed for control specimens (TBSUNT = 12.5 MPa, TBSCUNT = 9.0 MPa), specimens treated with argon-ion bombardment (TBSBAI = 10.3 MPa) and gas plasma (TBSGP = 11.0 MPa). A decrease of TBS was observed also for specimens treated with piranha solution (TBSPS = 3.9 MPa, TBSCPS = 4.1 MPa). A significant difference in TBS after three days storage was observed for specimens treated with different methods ( p < 0.001). Thermal cycling significantly reduced TBS for all groups ( p < 0.001) excluding groups: AAP( p > 0.05), CAAP( p > 0.05) and SC( p > 0.05). However, the failure patterns of debonded specimens prepared with 150-μm abrasive zirconia particles were 96.7% cohesive. Conclusion: Treatment of zirconia ceramic surfaces with abrasive zirconia particles is a promising method to increase the tensile bond strength without significant damage of the ceramic surface itself. An alternative promising method is slip casting.